Dysphagia incidence in intensive care unit patients with coronavirus disease 2019: retrospective analysis following systematic dysphagia screening. Issue 12 (22nd December 2022) - Zuercher, P; Lang, B; Moser, M; Messmer, A S; Waskowski, J; Schefold, J C
Abstract: Objective: Post-extubation dysphagia in critically ill patients is known to affect about 18 per cent of mixed medical-surgical intensive care unit patients. This study investigated the incidence of post-extubation dysphagia in adult intensive care unit patients with coronavirus disease 2019. Method: This study was a retrospective analysis of consecutive intensive care unit patients prospectively screened for dysphagia. Systematic screening of all extubated intensive care unit patients at our tertiary centre was performed using the Bernese intensive care unit dysphagia algorithm. The primary outcome measure was the incidence of post-extubation dysphagia. Results: A total of 231 critically ill adult coronavirus disease 2019 positive patients were included, and 81 patients remained in the final analysis after exclusion criteria were applied (e.g. patients transferred). Dysphagia screening positivity was 25 of 81 (30.9 per cent), with 28.2 per cent (22 of 78) having confirmed dysphagia by specialist examination within 24 hours ( n = 3 lost to follow up). Conclusion: In this observational study, it was observed that the incidence of dysphagia in adult critically ill coronavirus disease 2019 patients was about 31 per cent (i.e. increased when compared with a historical pre-pandemic non-coronavirus disease 2019 intensive care unit cohort).